Gender differentiation in the corporate environment: An analysis from recruitment to exercise at work (Research, Society and Development, 2023)
Gender differentiation in the specific context of the corporate scope is an important topic to understand not only what is taken into account in recruitment, but also the conditions and experiences in the exercise of the position. Moreover, this differentiation has an impact on society as a whole. Therefore, the objective was to understand the process of these people in the labor market, the performance in the position and the social practice. The research method was carried out through an integrative review, in which we sought to explore and synthesize the theme based on previous studies that addressed the central question of the research in a specific period of time, such as in the last five years. Based on the exploratory analysis, eight articles were obtained from the journal databases of Capes and academic Google. It was concluded that, despite the persistence of gender inequality in the corporate environment, significant changes were also observed in the political field. These changes are related to society and organizational practices, seeking to move away from views that normalize and standardize, which directly affects the treatment and rights of women and LGBTQIAP+ people.